"Clinical status and mortality in older adults with type 1 diabetes: Results from a public health system". (March 2022) - Moreno-Fernandez, Jesus; Sastre, Julia; Pinés, Pedro; del Val, Florentino; Calderon-Vicente, Dulce; Quiroga, Ivan; Herranz, Sandra; Lopez Gallardo, Gema; Gonzalez, Javier; Muñoz-Rodriguez, Jose-Ramón
Highlights: Understanding risk factors for cardiovascular disease among older adult patients with diabetes becomes increasingly important. Information concerning cardiovascular risk factors among older adult patients with type 1 diabetes mellitus is scarce. We evaluate clinical status and mortality of long-standing diabetes patients along a 10-yr period. Long-standing type 1 diabetes patients improved glycemic control although a worsening of cardiovascular risk factors was detected. In fact, observed mortality was higher in this group of patients. Abstract: Aim: To evaluate clinical status and mortality in older adults with long-standing type 1 diabetes mellitus (T1D). Methods: Cross-sectional analysis of all patients with T1D for 50 years or more from a cohort followed since 2010 at Castilla-La Mancha Public Health Service (Spain). Primary outcome was HbA1c change during the follow-up (2010–2020 period). Secondary outcomes included evaluation of insulin and continuous glucose monitoring (CGM) use, cardiovascular risk factors (CVRF), diabetes chronic complications and mortality. Results: A total of fifty-five T1D patients were analysed. Mean age was 69.5 ± 8.3 yrs. and T1D duration of 54.7 ± 4.7 yrs. We detected a HbA1c reduction of −0.5% (-6 mmol/mol) [95% CI −0.1, −0.9 (-2, −10); P = 0.016]. CGM was used by 26% of the patients. More patients suffered from hypertension and obesity in 2020 (66% vs. 78%, P = 0.016; and 26% vs. 31%, P = 0.016; respectively). An increase of diabetic polyneuropathy was detected (45% vs. 67%, P = 0.008). Rate of mortality was higher among patients with long-standing T1D (26% vs. 3.5%, P < 0.001), due to cardiovascular disease (57%). Conclusions: Older adults with long-standing T1D patients improved glycemic control although a worsening of CVRF and higher mortality rate were detected.